TECHNOLOGICAL VARIABLES OF RATIONING RESOURCES FOR TRANSPORTATION ON THE RAILROAD - Mykhalchenko, O. O. (Science and Transport Progress, 2008)
The basic components of the resources directed on performance of transportation process on the railway are presented. The basic technological variables used in rating of resources for the railway primary activity are determined.